2012
DOI: 10.1371/journal.pgen.1002503
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glypicans in Wnt Inhibitory Factor-1 Activity and the Structural Basis of Wif1's Effects on Wnt and Hedgehog Signaling

Abstract: Proper assignment of cellular fates relies on correct interpretation of Wnt and Hedgehog (Hh) signals. Members of the Wnt Inhibitory Factor-1 (WIF1) family are secreted modulators of these extracellular signaling pathways. Vertebrate WIF1 binds Wnts and inhibits their signaling, but its Drosophila melanogaster ortholog Shifted (Shf) binds Hh and extends the range of Hh activity in the developing D. melanogaster wing. Shf activity is thought to depend on reinforcing interactions between Hh and glypican HSPGs. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 105 publications
3
56
0
1
Order By: Relevance
“…S2B,BЈ). The long-range dispersion of Shf is in agreement with its reported dependence on Hh movement through the ECM in the wing disc (Glise et al, 2005;Gorfinkiel et al, 2005;Avanesov et al, 2012).…”
Section: Evolutionary Divergence Between Human Wif1supporting
confidence: 87%
See 3 more Smart Citations
“…S2B,BЈ). The long-range dispersion of Shf is in agreement with its reported dependence on Hh movement through the ECM in the wing disc (Glise et al, 2005;Gorfinkiel et al, 2005;Avanesov et al, 2012).…”
Section: Evolutionary Divergence Between Human Wif1supporting
confidence: 87%
“…In agreement with these data, overexpression of Shf in the P compartment of the wing disc results in an extension of the Hh gradient (see Fig. 6A; supplementary material Table S2) without affecting Wg signaling (Glise et al, 2005;Gorfinkiel et al, 2005;Avanesov et al, 2012) (Fig. 3B,BЈ).…”
Section: Evolutionary Divergence Between Human Wif1supporting
confidence: 83%
See 2 more Smart Citations
“…The differential expression of GPC3 can be used to differentiate and diagnose lung squamous cell carcinoma and lung adenocarcinoma. Basic research has indicated that GPC3 regulates the proliferation, differentiation, adhesion, and migration of tumor cells by modulating the insulin-like growth factor and wingless/integrated signaling pathways (Avanesov et al, 2012;Sakane et al, 2012;Pez et al, 2013;Dwivedi et al, 2013;Avanesov and Blair, 2013), thus playing important roles in tumor growth and metastasis. Stronger GPC3 expression has been correlated with increased growth and metastatic potential (Tanaka et al, 2011;Gao and Ho, 2011).…”
Section: Discussionmentioning
confidence: 99%